2012
DOI: 10.3390/ijerph9010100
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Edentulism on Quality of Life among Elderly

Abstract: This study aimed was to test the association between quality of life and edentulism among elderly individuals in a city in southeastern Brazil. This cross-sectional study was carried out with 163 individuals aged 60 years or older, functionally independent and non-institutionalized. Data were collected with a questionnaire and oral examination. The edentulism was the dependent variable. The independent variables were sex, age, household income and quality of life (WHOQOL-Old) and their scores. To assess the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 16 publications
3
68
0
8
Order By: Relevance
“…Results from a study carried out in the Southeast region of Brazil suggested that social participation reduces the prevalence of edentulousness among the elderly population [27].…”
Section: Discussionmentioning
confidence: 99%
“…Results from a study carried out in the Southeast region of Brazil suggested that social participation reduces the prevalence of edentulousness among the elderly population [27].…”
Section: Discussionmentioning
confidence: 99%
“…One of the truncated forms of p63, DN-p63a, functions as a survival factor in epidermal cells. Not surprisingly, DNp63a has been found to have enhanced expression in 80% of SCCs, and was shown to function synergistically with HDAC1/2 to inhibit apoptosis (Rodrigues et al 2012). Importantly, pharmaceutical inhibitors of HDACs also induced growth arrest in SCC cell lines, suggesting that HDACs are potential pharmaceutical targets for the treatment of skin cancers (Saunders et al 1999).…”
Section: The Role Of Histone Acetylation In Epidermal Differentiationmentioning
confidence: 99%
“…Todos os indivíduos devem ter uma saúde oral adequada que lhes permita falar, mastigar, reconhecer sabores, sorrir, viver sem dor ou desconforto e inter-relacionar com outras pessoas sem constrangimento [5,16,17].…”
Section: Metodologiaunclassified
“…Uma condição bucal deficiente, como a ausência dentária, contribui diretamente para a restrição da alimentação, participando como um fator negativo em suas atividades sociais e, muitas vezes, isola o indivíduo do convívio social [4,5].…”
Section: Introductionunclassified